Predictors of response to tenofovir disoproxil fumarate plus peginterferon alfa‐2a combination therapy for chronic hepatitis B. Issue 9 (15th September 2016) - Marcellin, P.; Ahn, S. H.; Chuang, W.‐L.; Hui, A. J.; Tabak, F.; Mehta, R.; Petersen, J.; Lee, C.‐M.; Ma, X.; Caruntu, F. A.; Tak, W. Y.; Elkhashab, M.; et al.
Summary: Background: In patients with chronic hepatitis B, tenofovir disoproxil fumarate (TDF) plus pegylated interferon (PEG‐IFN) for 48‐weeks results in higher rates of hepatitis B surface antigen (HBsAg) loss than either monotherapy. Aim: To identify baseline and on‐treatment factors associated with HBsAg loss at Week 72 and provide a model for predicting HBsAg loss in patients receiving combination therapy for 48 weeks. Methods: A secondary analysis of data from an open‐label study where patients were randomised to TDF (300 mg/day, oral) plus PEG‐IFN (PI, 180 μg/week, subcutaneous) for 48 weeks (TDF/PI‐48w); TDF plus PEG‐IFN for 16 weeks, TDF for 32 weeks (TDF/PI‐16w+TDF‐32w); TDF for 120 weeks (TDF‐120w) or PEG‐IFN for 48 weeks (PI‐48w). Logistic regression methods were used to identify models that best predicted HBsAg loss at Week 72. Results: Rates of HBsAg loss at Week 72 were significantly higher in the TDF/PI‐48w group (6.5%) than in the TDF/PI‐16w+TDF‐32w (0.5%), TDF‐120w (0%) and PI‐48w (2.2%) groups ( P = 0.09). The only baseline factor associated with response was genotype A. HBsAg decline at Week 12 or 24 of treatment was associated with HBsAg loss at Week 72 ( P < 0.001). HBsAg decline >3.5 log10 IU/mL at Week 24 in the TDF/PI‐48w group resulted in a positive predictive value of 85% and a negative predictive value of 99% for HBsAg loss at Week 72. Conclusions: HBsAg decline at Week 24 of TDF plus PEG‐IFN combination therapy may identify patients who, after completing 48 weeks of treatment, have a better chance of achieving HBsAg loss at Week 72.